Mixed single-layer and self-alignment technology of organic light-emitting diodes and multi-functional integration in organic devices. (7th May 2020) - Okada, Hiroyuki; Naka, Shigeki
Abstract: Mixed-single layer and self-alignment technology of organic light-emitting diodes and multi-functional integration in organic devices have been reviewed. For the fabrication of solution-processed organic light-emitting diodes, the structure of the mixed-single layer is simple and the selection of small organic molecules is superior than that of polymer organic material because many researchers are actively studying the chemical synthesis. From an aspect in the application of the organic devices, multi-functional abilities of an emission, a sensing and an integration are necessary. In this paper, we have collected up reported devices and concepts in the field of organic electronics.